2014
DOI: 10.11648/j.ijmea.20140206.16
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Experimental of Oil-Water Flow with Effect of Heat Transfer in Horizontal Pipe

Abstract: Abstract:There is a strong tendency for two immiscible fluids to arrange themselves so that the low viscosity constituent is in the region of high share. Therefore, it may be possible to introduce a beneficial effect in any flow of a very viscous liquid by introducing amount of a fluid lubricated as liquid-liquid oil-water flow. Two main classes of flows are seen, annular and small bubble in all experimental results. The pressure drop and mean heat-transfer coefficients were observed to depend strongly on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Simulation results were validated with horizontal literature data, and good conformity was observed. Abed and Auda 14 conducted an experimental and simulation study of oil–water flow inside the horizontal pipe to investigate heat transfer effects on the same. Yuan et al 15 suggested a novel real-gas model for characterizing and predicting gas leakage in pipelines where gas is flowed at high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results were validated with horizontal literature data, and good conformity was observed. Abed and Auda 14 conducted an experimental and simulation study of oil–water flow inside the horizontal pipe to investigate heat transfer effects on the same. Yuan et al 15 suggested a novel real-gas model for characterizing and predicting gas leakage in pipelines where gas is flowed at high pressures.…”
Section: Introductionmentioning
confidence: 99%